2020
DOI: 10.1002/jcp.30047
|View full text |Cite|
|
Sign up to set email alerts
|

Expression of Concern: Th17 and Treg cells function in SARS‐CoV2 patients compared with healthy controls

Abstract: In the course of the coronavirus disease 2019 (COVID‐19), raising and reducing the function of Th17 and Treg cells, respectively, elicit hyperinflammation and disease progression. The current study aimed to evaluate the responses of Th17 and Treg cells in COVID‐19 patients compared with the control group. Forty COVID‐19 intensive care unit (ICU) patients were compared with 40 healthy controls. The frequency of cells, gene expression of related factors, as well as the secretion levels of cytokines, were measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
154
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 142 publications
(167 citation statements)
references
References 49 publications
8
154
2
Order By: Relevance
“…CD4 + T cells consist of several subpopulations, such as Th1, Th17, and Treg cells, and a better understanding of different subpopulations of CD4 + T cells could better manage the patients with COVID-19. Sadeghi et al showed that critical COVID-19 patients had a higher frequency of Th17 and Th17/Treg cell ratio compared with healthy adults [24]. In contrast, we demonstrated that critical COVID-19 patients had significantly lower Th17 and Th17/Treg cell ratios compared with both healthy and moderate/severe groups.…”
Section: Discussioncontrasting
confidence: 64%
“…CD4 + T cells consist of several subpopulations, such as Th1, Th17, and Treg cells, and a better understanding of different subpopulations of CD4 + T cells could better manage the patients with COVID-19. Sadeghi et al showed that critical COVID-19 patients had a higher frequency of Th17 and Th17/Treg cell ratio compared with healthy adults [24]. In contrast, we demonstrated that critical COVID-19 patients had significantly lower Th17 and Th17/Treg cell ratios compared with both healthy and moderate/severe groups.…”
Section: Discussioncontrasting
confidence: 64%
“…Given the role of the immune system in defense against SARS-CoV2 as well as the viral immunopathogenesis, targeting immune responses such as suppressing Th1 and Th17 cell responses and augmenting the Treg cell responses can be effective in reducing the inflammation and accelerating the rehabilitation and recovery process in infected patients [ 25 ]. The reduced frequency and dysfunction of Treg cells in the course of SARS-CoV2 infection lead to disease progression, respiratory system injury, and ARDS [ 26 , 27 ]. Also, the enhanced number of naive T helper cells and downregulated frequency of Treg cells [mainly induced Treg (iTreg) cells] were detected in severe COVID-19 patients and proposed the essential roles of these cells in disease immunopathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on Treg cells in COVID-19 patients are insufficient, but some reports showed that Treg cells within peripheral blood mononuclear cells (PBMCs) of COVID-19 patients were decreased [ 10 , 11 ], while other reports found a relative increase in COVID-19 patients with severe disease or/and lymphopenia [ 12 , 13 ]. If the decreased Treg cells in PBMCs are due to the pulmonary recruitment of these cells along with Teff cells [ 15 ], which is one of the potential reasons for lymphopenia in severe COVID-19 patients [ 6 ], perhaps we should ask why aged patients do not have less lung inflammation compared to young COVID-19 patients, since those aged Treg cells have relatively enhanced suppression function [ 79 ].…”
Section: How Does Age-related Thymic Involution and Subsequent T-cmentioning
confidence: 99%
“…Th1-biased cellular immune responses typically direct the killing of the virus, while Th2-biased responses are usually associated with lung allergy in respiratory infections [ 9 ]. The roles of Treg cells reported during COVID-19 are thus far contradictory, either reportedly decreased [ 10 , 11 ] or relatively increased in COVID-19 patients with severe disease or/and lymphopenia [ 6 , 12 , 13 ]. The roles of Treg cells in COVID-19 patients should perhaps be assessed based on their physiological localization and disease stage.…”
Section: Introductionmentioning
confidence: 99%